Coastal tourism and beach sustainability – an assessment of community perceptions in Kovalam, India - Proshanta Kumar Ghosh,; Debajit Datta, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
Coastal areas are among the most densely populated zones worldwide and at the same time subjected to rapid environmental changes due to their land-sea interface locations. The phenomenal growth of coastal tourism in the last few decades, especially in the tropical countries, has created environmental havocs by drastically altering the local ecological milieu in which the indigenous communities have thrived for generations. Kovalam, a coastal village of Kerala, India, has been studied to assess the status of beach dependent tourism and its impact on the sustainability of beaches in the long run through participatory community appraisals. It was found that standing on the thin line between survival and destruction, the coastal village of Kovalam needs more such initiatives from all corners of the society to protect itself from the havocs created by the consumerist urban-industrial culture. In this context sSeveral development oriented guidelines were forwarded to initiate ecofriendly tourism, primarily based on local community endeavors, which will in turn enhance the local resource pool.